2016
DOI: 10.14710/jgi.4.2.131-137
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh jamur tiram putih (pleurotus ostreatus) terhadap kadar glukosa darah, profil lipid dan kadar MDA pada tikus (rattus norvegicus) diabetes melitus

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Specifically, Oyster-D potentially influenced glucose metabolism by enhancing insulin sensitivity and secretion within the body. This effect occurred through the activation of vitamin D receptors present on pancreatic β-cells, as suggested by Kardina et al 21 Additionally, vitamin D possessed the ability to mitigate systemic inflammation and enhance insulin resistance, as highlighted by Lee et al 22 Purbowati et al, 9 stated that the administration of oyster mushroom extract at a dosage of 200 mg/kg body weight showed greater efficacy in lowering blood glucose levels. This result provided evidence of the impact of white oyster mushroom powder, rich in vitamin D, on reducing blood glucose.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, Oyster-D potentially influenced glucose metabolism by enhancing insulin sensitivity and secretion within the body. This effect occurred through the activation of vitamin D receptors present on pancreatic β-cells, as suggested by Kardina et al 21 Additionally, vitamin D possessed the ability to mitigate systemic inflammation and enhance insulin resistance, as highlighted by Lee et al 22 Purbowati et al, 9 stated that the administration of oyster mushroom extract at a dosage of 200 mg/kg body weight showed greater efficacy in lowering blood glucose levels. This result provided evidence of the impact of white oyster mushroom powder, rich in vitamin D, on reducing blood glucose.…”
Section: Resultsmentioning
confidence: 96%
“…8 Various types of mushrooms, such as maitake, shiitake, oyster, and other species, have high levels of vitamin D precursor when exposed to sunlight. 9 According to Hussana, 5 the exposure of oyster mushrooms to UV-B light increased the vitamin D2 level to more than 11 micrograms/gram. UV-B light exposure enhances vitamin D production in mushrooms without altering their nutritional composition, making the process safe to carry out.…”
mentioning
confidence: 99%
“…These results support previous studies, which stated that administering oyster mushroom powder and extract could reduce FBG levels and improve pancreatic beta cells in dia- o n l y betic rats. 32,33 Another in-vivo study in mice and rats fed with a high-fat diet showed that administering Pleurotus citrinopileatus and Pleurotus tuber-regium extracts could reduce fasting blood glucose levels. 19,34 Administering β-glucan from sources such as oats and chitin reduces FBG and HOMA-IR levels insulin secretion and repairs pancreatic beta cells.…”
Section: Resultsmentioning
confidence: 99%
“…β-glucan becomes a potent molecule to improve glucose homeostasis in the body through hypoglycemic effects, improvement of insulin resistance, and decreased apoptosis of pancreatic cells. 15,32,34 Decreased pro- inflammatory cytokines also improved insulin resistance, where low IL-6 and IL-1β increased the expression and sensitivity of insulin receptor substrate, specifically IRS-1. This resulted in increased insulin-mediated glucose uptake into cells.…”
Section: Resultsmentioning
confidence: 99%
“…After 5 days post-induction of STZ-NA, the rats fasted for eight hours before taking blood through the retro-orbital flexus. Rats with hyperglycemic conditions with fasting blood glucose levels >150 mg/dL and changes in lipid profile were used as study samples [28][29][30] .…”
Section: Experimental Animal Induction and Treatmentmentioning
confidence: 99%